An object-oriented approach to simulating human gait motion based on motion tracking - Tändl, Martin; Stark, Tobias; Erol, Nihat Ercümet; Löer, Franz; Kecskeméthy, Andrés (Zielona Góra: Uniwersytet Zielonogórski)
Accurate bone motion reconstruction from marker tracking is still an open and challenging issue in biomechanics. Presented in this paper is a novel approach to gait motion reconstruction based on kinematical loops and functional skeleton features extracted from segmented Magnetic Resonance Imaging (MRI) data. The method uses an alternative path for concatenating relative motion starting at the feet and closing at the hip joints.
Keywords: gait/motion analysis; muskuloskeletal system; multibody simulation; MRI; X-ray; motion tracking